Assessing the Quality of Traditional Street in Indonesia: A case study of Pasar Baru Street. (31st October 2016) - Sholihah, Arif Budi; Heath, Tim
Abstract: This paper attempts to assess the quality of a traditional street in Indonesia especially from the diversity indicator and also explores the role of diversity in the quality of life of such urban historical street. A qualitative inquiry is undertaken utilising field observations and in-depth interviews. The findings show four diversity components - land use, retail use, ethnic group, and special skills diversity - contribute to the heterogeneity of the case study. It is also revealed that the ethnic diversity has not only impacted upon the heterogeneity of retail use but also contributes to the innovation of products as a result of a hybrid culture, such as culinary or art products.